Is Contralateral Templating Reliable for Establishing Rotational Alignment During Intramedullary Stabilization of Femoral Shaft Fractures? A Study of Individual Bilateral Differences in Femoral Version. Issue 2 (February 2018) - Croom, William P.; Lorenzana, Daniel J.; Auran, Richard L.; Cavallero, Matthew J.; Heckmann, Nathanael; Lee, Jackson; White, Eric A.
Abstract : Objectives: To determine native individual bilateral differences (IBDs) in femoral version in a diverse population. Methods: Computed tomography scans with complete imaging of uninjured bilateral femora were used to determine femoral version and IBDs in version. Age, sex, and ethnicity of each subject were also collected. Femoral version and IBDs in version were correlated with demographic variables using univariate and multivariate regression models. Results: One hundred sixty-four subjects were included in the study. The average femoral version was 9.4 degrees (±9.4 degrees). The mean IBD in femoral version was 5.4 degrees (±4.4 degrees, P < 0.001). A total of 17.7% of subjects had a difference in version ≥10 degrees, and 4.3% had a difference in version ≥15 degrees. A femur with anteversion ≥20 degrees or retroversion was associated with a greater mean difference in version from the contralateral side compared with those with midrange anteversion. Conclusions: Bilateral differences in femoral version are common and can result in a difference from native anatomy that may be clinically significant if only the contralateral limb is used to establish rotational alignment during intramedullary stabilization of diaphyseal femur fractures. This is also an important consideration when considering malrotation of femur fractures because most studies define malrotation as a greater than 10–15-degree difference compared with the contralateral side. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.